Cost and environmental impact estimation methodology and potential impact factors in offshore oil and gas platform decommissioning: A review - Tan, Y.; Li, H.X.; Cheng, J.C.P.; Wang, J.; Jiang, B.; Song, Yongze; Wang, Xiangyu (2021)
© 2020 Elsevier Inc.